Analisis Tingkat Kepuasan Konsumen Terhadap Bawang Merah Organik (Allium Ascalonicum L) di Kebun Praktek Fakultas Teknologi Pangan, Pertanian dan Perikanan Universitas Nusa Nipa - Rina, Sr. Maria Herlina (Jurnal Ilmiah Wahana Pendidikan, 2024)
Consumer satisfaction is the perceived result of using products and services that equals or exceeds desired expectations. To create customer satisfaction, companies must create and manage a system to obtain more customers with the ability to retain customers. The aim of this research is to determine the level of consumer satisfaction of organic shallots in practice gardens, Faculty of Agricultural Food Technology and Fisheries, Nusa Nipa University. Sampling was taken using the Accidental Sampling method. Sampling technique based on chance. The number of samples in this study was 30 people. The collected data was analyzed using a descriptive method which was carried out to determine the existence of independent variables, either only on one variable or more without making comparisons or connecting them with other variables. Also uses the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) analysis methods. The research results showed that the consumer satisfaction index value was 0.91 or 91%, where this value was in the range 0.81–1.00. According to testing rules, the overall level of satisfaction is obtained with a result of 0.51 – 1.00. then accept H1, which means consumers are satisfied with the level of performance on the attributes provided by the practice garden of the Faculty of Food, Agriculture and Fisheries Technology as a whole.